2019
DOI: 10.1016/j.optcom.2019.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interferometry via a coherent state mixed with a photon-added squeezed vacuum state

Abstract: We theoretically investigate the phase sensitivity with parity detection on a Mach-Zehnder interferometer with a coherent state combined with a photon-added squeezed vacuum state. When the phase shift approaches zero, the squeezed vacuum state is indeed the optimal state within a constraint on the average number of photons. However, when the phase shift to be estimated slightly deviates from zero, the optimal state is neither the squeezed vacuum state nor the photonsubtracted squeezed vacuum state, but the pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A plethora of quantum states have been shown to have a quantum metrological interest [1,14,[30][31][32][33][45][46][47][48][49][50][51]. The discussions however, were carried out in the balanced case only, with few exceptions [24][25][26].…”
Section: Gaussian and Non-gaussian Input State Examplesmentioning
confidence: 99%
“…A plethora of quantum states have been shown to have a quantum metrological interest [1,14,[30][31][32][33][45][46][47][48][49][50][51]. The discussions however, were carried out in the balanced case only, with few exceptions [24][25][26].…”
Section: Gaussian and Non-gaussian Input State Examplesmentioning
confidence: 99%
“…Quantum mechanical states of light have been studied extensively in the field of quantum metrology [1][2][3][4][5][6][7] , where one is interested in performing highly resolved and sensitive measurements of signals like, for example, what one would expect to detect from gravitational waves 8 (also see Barsotti et al 9 and references therein) or for the precise measurement of transition frequencies in atomic (ion) spectroscopy 10 . The advantage one gains over using classical fields is the ability to exploit inherently quantum characteristics of the state such as entanglement, squeezing or some other non-classical property 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, optical interferometers have been widely used to estimate very small phase shifts in both theoretical and experimental studies on quantum metrology. For a Mach-Zehnder interferometer (MZI) with nonclassical input states [1,2,3,4,5,6,7,8,9,10], the sensitivity of the phase estimation can surpass the shot-noise limit (SNL), ∆φ = 1/ √ n [1], even approach the so-called Heisenberg limit (HL) ∆φ = 1/n [11,12], where n is the mean number of photons inside the interferometer. An MZI is also called an SU(2) interferometer, as Yurke et al in 1986 showed that the group SU (2) can naturally describe an MZI [13].…”
Section: Introductionmentioning
confidence: 99%